Transport Properties of the Simple Lennard-Jones/Spline Fluid I: Binary Scattering and High-Accuracy Low-Density Transport Coefficients - Kristiansen, Kim R. (Frontiers in Physics, 2020)
Inspired by recent work on the thermodynamic properties of the Lennard-Jones/spline (LJ/s) fluid, we have considered the transport properties of the simple LJ/s fluid. The binary scattering problem for LJ/s particles was solved numerically, and results were compared to the untruncated LJ fluid. The scattering dynamics are affected both by the restricted range of the LJ/s potential, and the stronger attraction between LJ/s particles at distances between the inflection point of the potential and the cutoff range. At small relative kinetic energies, it was found that the scattering cross section of the LJ/s particles is much smaller than that of the LJ particles. The shear viscosity, thermal conductivity, and the self-diffusion coefficient were calculated from the scattering cross sections by the Chapman-Enskog method, and a six-parameter equation with a worst case accuracy of roughly 1 % over the temperature interval [0.1,1000] in LJ units is provided. The smaller scattering cross section at low kinetic energies leads to transport coefficients of the LJ/s fluid to be greater than those of the LJ fluid at low temperatures, and were all found to be roughly 50 % greater at T = 0.1, which is the lowest temperature considered.